T-cell regulation in Erythema Nodosum Leprosum. - Edessa Negera; Stephen L Walker; Kidist Bobosha; Rawleigh Howe; Abraham Aseffa; Hazel M Dockrell; Diana N Lockwood (Public Library of Science (PLoS), 2017)
Leprosy is a disease caused by Mycobacterium leprae where the clinical spectrum correlates with the patient immune response. Erythema Nodosum Leprosum (ENL) is an immune-mediated inflammatory complication, which causes significant morbidity in affected leprosy patients. The underlying cause of ENL is not conclusively known. However, immune-complexes and cell-mediated immunity have been suggested in the pathogenesis of ENL. The aim of this study was to investigate the regulatory T-cells in patients with ENL. Forty-six untreated patients with ENL and 31 non-reactional lepromatous leprosy (LL) patient controls visiting ALERT Hospital, Ethiopia were enrolled to the study. Blood samples were obtained before, during and after prednisolone treatment of ENL cases. Peripheral blood mononuclear cells (PBMCs) were isolated and used for immunophenotyping of regulatory T-cells by flow cytometry. Five markers: CD3, CD4 or CD8, CD25, CD27 and FoxP3 were used to define CD4+ and CD8+ regulatory T-cells. Clinical and histopathological data were obtained as supplementary information. All patients had been followed for 28 weeks. Patients with ENL reactions had a lower percentage of CD4+ regulatory T-cells (1.7%) than LL patient controls (3.8%) at diagnosis of ENL before treatment. After treatment, the percentage of CD4+regulatory T-cells was not significantly different between the two groups. The percentage of CD8+ regulatory T-cells was not significantly different in ENL and LL controls before and after treatment. Furthermore, patients with ENL had higher percentage of CD4+ T-ells and CD4+/CD8+ T-cells ratio than LL patient controls before treatment. The expression of CD25 on CD4+ and CD8+ T-cells was not significantly different in ENL and LL controls suggesting that CD25 expression is not associated with ENL reactions while FoxP3 expression on CD4+ T-cells was significantly lower in patients with ENL than in LL controls. We also found that prednisolone treatment of patients with ENL reactions suppresses CD4+ T-cell but not CD8+ T-cell frequencies. Hence, ENL is associated with lower levels of T regulatory cells and higher CD4+/CD8+ T-cell ratio. We suggest that this loss of regulation is one of the causes of ENL.